Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10439-015-1292-9
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Characterization of a Model of Noninvasive, Traumatic Anterior Cruciate Ligament Injury in the Rat

Abstract: The onset of post-traumatic osteoarthritis (PTOA) remains prevalent following traumatic joint injury such as anterior cruciate ligament (ACL) rupture, and animal models are important for studying the pathomechanisms of PTOA. Noninvasive ACL injury using the tibial compression model in the rat has not been characterized, and it may represent a more clinically relevant model than the common surgical ACL transection model. This study employed four loading profiles to induce ACL injury, in which motion capture ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 35 publications
0
44
0
Order By: Relevance
“…Evidence supporting the existence of underlying acute biologic phenomena at the time of ACL injury that precipitate rapid joint degeneration continues to emerge . In the present study, we applied high‐resolution 1 H‐NMR spectroscopy and DI‐MS to measure metabolite concentrations in the serum of rats subjected to a validated, non‐surgical ACL rupture protocol . We found that several carnitine and tryptophan metabolites distinguished ACLR from Control rats, and AUROC analysis of the top two LASSO regression‐identified metabolites at each time point demonstrated predictive accuracies of 76.8%, 96.8%, and 87.8% at 72 h, 4 weeks and 10 weeks, respectively.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Evidence supporting the existence of underlying acute biologic phenomena at the time of ACL injury that precipitate rapid joint degeneration continues to emerge . In the present study, we applied high‐resolution 1 H‐NMR spectroscopy and DI‐MS to measure metabolite concentrations in the serum of rats subjected to a validated, non‐surgical ACL rupture protocol . We found that several carnitine and tryptophan metabolites distinguished ACLR from Control rats, and AUROC analysis of the top two LASSO regression‐identified metabolites at each time point demonstrated predictive accuracies of 76.8%, 96.8%, and 87.8% at 72 h, 4 weeks and 10 weeks, respectively.…”
Section: Discussionmentioning
confidence: 73%
“…Throughout the study, rats were allowed ad libitum cage activity and provided unlimited access to food and water. ACLR rats were subjected to a tibial compression‐based noninvasive ACL rupture protocol, as previously described . Briefly, rats were immobilized in prone position on a custom fixture on a materials testing system (Insight 5, MTS Systems, Eden Prairie, MN).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immediately prior to injury, rats were administered 5 mg/kg subcutaneous Carprofen, anesthetized with intraperitoneal ketamine/xylazine, and maintained under 1-2% inhaled isoflurane. Noninvasive ACLR was induced using tibial compression-based mechanical loading, as previously described 25-27 . Rats were positioned prone on a custom fixture, with the right knee in ∼100° of flexion.…”
Section: Methodsmentioning
confidence: 99%